Bridge design for inspection and maintenance – a UK and US perspective. Issue 4 (5th September 2019) - Colford, Barry R.; Beabes, Shane R.; Bulmer, Mark J.
Abstract : Over the past few decades, engineers working in design offices have become much better at designing for constructability. The use of the design and build form of procurement has, in many ways, been instrumental in this change. The use of accelerated bridge construction in the USA, although primarily a method of reducing traffic impact, has also helped engineers become better at designing for constructability. However, it can be argued that engineers have not made the same progress in designing bridges to make future inspections and maintenance easier. In fact, unless an employer's requirements for inspection and maintenance are clearly prescribed in detail in the contract, then the design and build form of procurement is perhaps the least advantageous when considering the service life of a structure. Over the lifespan of a bridge, the service life costs, including inspection and maintenance, can account for a significant percentage of the lifecycle costs of the bridge. Therefore, the importance of not only ensuring that an adequately funded proper inspection and maintenance regime is established but also that sufficient attention is paid to the provision of inspection and maintenance during the design stage cannot be overstated. This paper examines and compares current practice in the UK and USA and considers ways of improving the design process to assist the future inspection and maintenance of bridges.